2013
DOI: 10.1097/01.pra.0000438184.74359.88
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Practitioners’ Use and Attitudes Regarding the Internet and Social Media

Abstract: Mental health care professionals are starting to incorporate Internet technologies into their professional lives, but they remain divided on the ethics and utility of using these technologies in clinical care. There appear to be differences in practices and attitudes toward the Internet among clinicians with different levels of experience and in different practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Screening the current literature, it becomes obvious that there are areas where Skype conferences have now become essential and have proven just as effective by maintaining total patient satisfaction and a salient outcome: mental healthcare professionals have increasingly incorporated Internet technologies into their professional lives, (14) and the American Speech-Language-Hearing Association has indicated that telehealth should be considered when attempting to address barriers to service provision and access (15). Similar to the positive results of these studies, our data show that videoconferencing is not only feasible and reliable in a highly specialized field such as ITX, but was also strongly supported by our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening the current literature, it becomes obvious that there are areas where Skype conferences have now become essential and have proven just as effective by maintaining total patient satisfaction and a salient outcome: mental healthcare professionals have increasingly incorporated Internet technologies into their professional lives, (14) and the American Speech-Language-Hearing Association has indicated that telehealth should be considered when attempting to address barriers to service provision and access (15). Similar to the positive results of these studies, our data show that videoconferencing is not only feasible and reliable in a highly specialized field such as ITX, but was also strongly supported by our patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line with such conclusions, a recent report from "The Telegraph" stated that telehealth has the potential to cut the annual 517 000 outpatient appointments by 35% and could prevent up to 180 000 people a year having to take time off work, travel to clinics, or find child care during appointments. The reforms toward telehealth and videoconferencing would therefore improve the lives of most patients and save Great Britain Pounds (GBP) 2.9 billion almost immediately (14).…”
Section: Discussionmentioning
confidence: 99%
“…Professionals in clinical settings differ in their views of the incorporation of technology into their practice [15] and vary in terms of their online presence [16]. If social media websites are associated with negative outcomes, it would be extremely useful to mental health practitioners to develop a keener understanding of these millions-strong vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, just one-third of commentators shared their commentary with colleagues, but a further one-fifth wanted to. EBMH could do more to facilitate this, perhaps using social media, as increasing numbers of researchers and clinicians use this as a platform for information sharing and discussion 11. We were eager to see how the new format of the commentaries compared with the old.…”
Section: Discussionmentioning
confidence: 99%